Mechanism for potential strengthening of Atlantic overturning prior to collapse - Ehlert, D.; Levermann, Anders (Prof. Dr.) (Earth System Dynamics, 2014)
The Atlantic meridional overturning circulation (AMOC) carries large amounts of heat into the North Atlantic influencing climate regionally as well as globally. Palaeo-records and simulations with comprehensive climate models suggest that the positive salt-advection feedback may yield a threshold behaviour of the system. That is to say that beyond a certain amount of freshwater flux into the North Atlantic, no meridional overturning circulation can be sustained. Concepts of monitoring the AMOC and identifying its vicinity to the threshold rely on the fact that the volume flux defining the AMOC will be reduced when approaching the threshold. Here we advance conceptual models that have been used in a paradigmatic way to understand the AMOC, by introducing a density-dependent parameterization for the Southern Ocean eddies. This additional degree of freedom uncovers a mechanism by which the AMOC can increase with additional freshwater flux into the North Atlantic, before it reaches the threshold and collapses: an AMOC that is mainly wind-driven will have a constant upwelling as long as the Southern Ocean winds do not change significantly. The downward transport of tracers occurs either in the northern sinking regions or through Southern Ocean eddies. If freshwater is transported, either atmospherically or via horizontal gyres, from the low to high latitudes, this would reduce the eddy transport and by continuity increase the northern sinking which defines the AMOC until a threshold is reached at which the AMOC cannot be sustained. If dominant in the real ocean this mechanism would have significant consequences for monitoring the AMOC.